Catalytic asymmetric diarylphosphine addition to α-diazoesters for the synthesis of P-stereogenic phosphinates via P*-N bond formation - Balázs, László B. (2022)
The asymmetric catalytic P-H addition of racemic secondary phosphines to electrophilic α-diazoesters via P*-N bond formation is disclosed for the first time. Interaction between the diazoester and the palladium catalyst resulted in the unusually enhanced electrophilic ability of the terminal nitrogen in the diazo functionality, as opposed to the commonly expected formation of a metal carbene by nitrogen elimination. Further derivatization of the generated phosphinic hydrazones provided access to enantioenriched P-stereogenic diarylphosphinates via a simple transformation.